Total Productive Maintenance Analysis of The Oven Machine Using Overall Equipment Effectiveness Method : (Case Study at CV. Halalan Thoyiban Bakery) - Muhammad Azyumiardi Azra; Khusna Dwijayanti (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2022)
The oven machine is one of the important components of the production process in the bakery company. CV Halalan Thoyiban is a bakery company engaged in the manufacture of various breads. The products of this company are various bread such as Bakpia Green Bean and Bakpia Green Coconut. The problem that occurs in the company is the low efficiency of bakpia bread production, caused by the large number of machine breakdowns so that the optimal level of machine productivity is not achieved. The production machine, especially the oven machine often breaks down and causes the production process to stop. Based on these problems, in this study, an analysis of Total Productive Maintenance (TPM) was carried out using the Overall Equipment Effectiveness (OEE) method to measure the effectiveness of the machine. Further analysis of the cause-and-effect diagram is conducted to propose the improvement recommendation. The results of the analysis show the Overall Equipment Effectiveness (OEE) for the oven machine obtained an average of 38.1%, where the activity measured at the availability index is 59.72%, the performance index is 68.90% and the quality ratio is 93.30%. The OEE value is low and does not meet the World Class standard. The main causes are large breakdowns and long maintenance processes. The first improvement recommendation is applying preventive maintenance based on the planned maintenance schedule. The second recommendation is providing a training to operators about machine operation and maintenance. And the last is providing a simple installation for gas cylinder to avoid the long changing time to maximize performance of the oven machine.